(untitled) (Research, Society and Development, 2022)
Currently, the use of videos in science classes is increasingly common. According to previous investigations, the documental genre is generally the most used because it presents the content in a clearer way and accords with reality. However, students often find this type of genre boring. So, what does it take for a film to work for a specific audience? The objective of this work was to understand the relation of knowledge mobilized during the production of videos, carried out by undergraduate students in Biological Sciences, aimed at primary students, and to clarify if the intended audience has placed itself, in fact, in the idealized place by video producers. For the production study, the generated videos were analyzed, as well as the interview carried out with the producers. During the reception stage, after the vídeos were shown, the questionnaires answered by the spectators were analyzed. The concept of message circularity in the communicative process and the audiovisual adressing, proposed by Stuart Hall and Elizabeth Ellsworth, respectively, serve as a basis for understanding the communicative process in the classroom. As a conclusion, the undergraduate students made conscious decisions, having in mind the target audience, and, despite the fact that the majority of the spectators had read the videos shown according to the ideas of the producers, there were some resistance points. These results indicate that there was a negotiation of meanings by the spectator, and these, in turn, actively participated in the construction of meaning within the communicative process.